2018
DOI: 10.1038/s41598-018-35796-4
|View full text |Cite
|
Sign up to set email alerts
|

The delta neutrophil index predicts development of multiple organ dysfunction syndrome and 30-day mortality in trauma patients admitted to an intensive care unit: a retrospective analysis

Abstract: No studies have examined the role of delta neutrophil index (DNI) reflecting on immature granulocytes in determining the severity of multiple organ dysfunction (MODS) and short-term mortality. This study investigated the utility of the automatically calculated DNI as a prognostic marker of severity in trauma patients who were admitted to an intensive care unit (ICU). We retrospectively analysed prospective data of eligible patients. We investigated 366 patients. On multivariable logistic regression analysis, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 33 publications
1
27
0
Order By: Relevance
“…Increased DNI at 12 hours was a strong independent predictor of shortterm mortality. In addition, the cut-off value of DNI at 12 hours to predict 30-day mortality was 5.3% in that study [18], which was similar to the result in our study. In this study, we found that although 62 (36.7%) patients had GI perforation, there was no significant difference in the mortality rate according to GI perforation (patients with GI perforation 8.1% vs. patients without GI perforation 13.1%, p = 0.319).…”
Section: Plos Onesupporting
confidence: 89%
See 1 more Smart Citation
“…Increased DNI at 12 hours was a strong independent predictor of shortterm mortality. In addition, the cut-off value of DNI at 12 hours to predict 30-day mortality was 5.3% in that study [18], which was similar to the result in our study. In this study, we found that although 62 (36.7%) patients had GI perforation, there was no significant difference in the mortality rate according to GI perforation (patients with GI perforation 8.1% vs. patients without GI perforation 13.1%, p = 0.319).…”
Section: Plos Onesupporting
confidence: 89%
“…Previous studies about surgical and medical patients showed that DNI was a useful biomarker to predict disease severity or prognosis in patients with various infections or sepsis [7,10,16,17]. However, studies about usefulness of DNI in patients who had tissue injury or hemorrhage due to trauma are limited [18]. Systematic inflammatory response syndrome (SIRS) is initiated within 30 minutes after severe injury, which is associated with an inflammatory response to hemorrhage or tissue damage rather than infections.…”
Section: Plos Onementioning
confidence: 99%
“… 22 A study by Kong et al . 23 conducted with trauma patients showed that IG% could be a marker of the 30-day mortality at >5.3% value. In another study, they found that severe sepsis and septic shock significantly increased in patients with an IG value > 6.5%.…”
Section: Discussionmentioning
confidence: 99%
“…(c) Organ failure: While few cases of organ failure are revealed in the overall circumstances, most of the deceased have developed organ failure, and a quarter of them shows the manifestation of DIC, which may cause patients to suffer from multiple organ failure (MOF) 6,22,29 . Nevertheless, compared with the general mortality of MOF patients induced by sepsis or trauma (39% to 62%), 36,37 the death rate in fish bile poisoning with MOF is relatively lower. (d) Treatment methods: It is a truism that the problem to be solved is to remove toxic substances inside the body since sufficient clearance of the toxins may improve prognosis 28 .…”
Section: Discussionmentioning
confidence: 99%